Life course explanations of consumer responses to threats: the case of COVID-19 - Sarinya L. Suttharattanagul; Yuanfeng Cai; George P. Moschis (Cogent Business & Management, 2022)
Marketing managers and researchers have had a long-standing interest in understanding the onset of new patterns of consumer behavior, but they have had few theoretical and methodological tools for studying the onset and stability of consumption patterns over the course of a person's life. The recently-developed multi-theoretical life course paradigm (LCP) has been increasingly used widely across disciplines to study change and continuity in behavior; it can be employed to help understand the onset of new patterns of consumer behavior. This article presents the conceptual life course model as a research framework based on the LCP for studying the development of new shopping and consumption patterns and shows how this framework could provide new insights that help better understand existing views on the development and change of consumer habits. Based on the LCP's multi-theoretical perspectives and previous research, the article develops hypotheses derived from the course model to help explain the onset and changes in consumption habits following the COVID-19 outbreak; and it uses an online sample of Thai consumers to test them. The results offer insights into change mechanisms that serve as bases for consumer behavior modification, and suggest implications for public policy, marketing practice, theory and further research.
Keywords: 650; COVID-19; life course paradigm; shopping patterns; Thailand